The Effectiveness of Botanical Pesticides from Soursop Leaves (Annona muricata L.) and Papaya Leaves (Carica papaya) on the Control of Brown Planthopper (Nilaparvata lugens) in Rice Plants (Oryza sativa L.) - Saifa Wardati; Nursayuti Nursayuti; Aidil Amar; Saniar Fauza; Marlina Marlina (Fakultas Pertanian Universitas Almuslim Bireuen Aceh, 2025)
This study aimed to determine the effectiveness of botanical pesticides from soursop leaf and papaya leaf extracts in controlling brown planthopper on rice plants. The research was conducted in Nien Village, Simpang Tiga District, Pidie Regency, from February to April 2025, using a factorial Randomized Block Design (RBD) with two factors. Factor I was soursop leaf extract concentration (S): S0 = 0 ml/l water, S1 = 100 ml/l water, and S2 = 200 ml/l water. Factor II was papaya leaf extract concentration (P): P0 = 0 ml/l water, P1 = 100 ml/l water, and P2 = 200 ml/l water. Observed parameters included mortality rate, attack intensity, plant height, number of tillers, number of panicles per clump, and grain weight per plot. The results showed that soursop leaf extract at 200 ml (S2) had a highly significant effect on pest mortality (84.72%), attack intensity after application (11.11%), plant height, number of tillers at 30 DAP, and grain weight per plot. Papaya leaf extract at 200 ml (P2) had a highly significant effect on pest mortality (68.05%), attack intensity after application (8.33%), plant height, number of tillers at 30 DAP, and number of panicles per clump. The combination of both extracts (S2P2) showed a highly significant interaction on attack intensity after application, plant height, and number of tillers at 30 DAP, and a significant effect on pest mortality, with the highest mortality (95.83%) and lowest attack intensity (0%) obtained in the S2P2 combination.